KCNQ2-Neonatal Epileptic Encephalopathy Complicated by Ventricular Tachycardia: A Case Report - Geng, Yuehang; Hou, Xinlin (Frontiers in Neurology, 2020)
Introduction: Mutations in KCNQ2 are related to a spectrum of neonatal epileptic phenotypes. Here we report a case of KCNQ2-related neonatal epileptic encephalopathy (KCNQ2-NEE) that is complicated by an incidentally found ventricular tachycardia. Case presentation: An infant boy presented with very early onset refractory focal tonic seizures and developmental delay, and was diagnosed with epilepsy. Trio-whole exome sequencing identified a previously reported de novo mutation in KCNQ2 [c.794C>T; p.(Ala265Val)], a known pathogenic variant for KCNQ2-NEE. Interestingly, ventricular tachycardia was incidentally found on electrocardiography. Conclusions: We here suggest the possibility of a potential electrophysiologic link between the two phenotypes and that they may be attributable to the same de novo mutation.